Respostas

2014-01-12T17:58:14-02:00
4x^4+4=17x^2
x^2= u
4u^2+4=17u
4u^2-17u+4=0

Sendo:
a= 4 b= -17 c=4
Δ= b²-4ac
Δ=(-17)²-4·4·4
Δ=289-64
Δ=225

u= -b+/- √Δ/2a
u= -(-17)+/-√225/2·4
u= 17+/-15/8

u'= 4
u''=2/8
Simplificando por 2
u''= 1/4

S:[ 1/4 , 4]
u = x² , logo u={1/4,4}

1/4 = x²
x' = raiz(1/4)
x' = +-1/2

4 = x²
x'' = raiz(4)
x'' = +-2

S={-2,-1/2,1/2,+2}
Biquadrada :)
;)
Eu que troquei agora, haha
huahua
Acho que está certo agora, ufa.
A melhor resposta!
2014-01-12T18:02:56-02:00
Considere x^{2} =y.

4x^2 - 17x^2+4 = 0 \\ 4y^2 - 17y + 4 =  \\  \Delta = b^2 - 4ac \\ \Delta = (-17)^2 - 4*4*4 \\ \Delta = 289 - 64 = 225

y =  \frac{-b \pm  \sqrt{\Delta}}{2a}
y = \frac{17 \pm \sqrt{225}}{2*4}

y' = \frac{17 + 15}{8} = 32/8 = 4

y'' = \frac{17 - 15}{8} = 2/8 = 1/4

Substituindo:
x^{2} =y
(1/4) =x^2
x' = 1/2; x''= -1/2

x^{2} =y
(4) =x^2
x''' = 2; x''''= -2

Logo, x' = 1/2, x'' = - 1/2x''' = 2x'''' = -2.

Espero ter ajudado!

3 5 3